DEVELOPMENT TRENDS OF UZBEKISTAN-KYRGYZ CULTURAL RELATIONS IN THE CONTEXT OF INTERNATIONAL RELATIONS IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2025)
This article provides a comprehensive analysis of interethnic relations in the Republic of Uzbekistan, the reforms implemented in this regard in the country, in particular, legislative initiatives, and the development trends of intercultural relations, in particular, Uzbek-Kyrgyz cultural relations, based on them.